2017
DOI: 10.1016/j.pmrj.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity Management: The Current State of Transcranial Neuromodulation

Abstract: V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 107 publications
(206 reference statements)
0
10
0
Order By: Relevance
“…It has been shown in the literature that five to 10 sessions of high‐frequency (HF)‐rTMS or intermittent theta‐burst stimulation (iTBS) of the primary motor cortex reduce spasticity by 18%–42% in patients with MS . Both protocols can reduce the level of spasticity by increasing the excitability of the primary motor cortex and as a result increasing the downward inhibitory effects of gamma motoneurons .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in the literature that five to 10 sessions of high‐frequency (HF)‐rTMS or intermittent theta‐burst stimulation (iTBS) of the primary motor cortex reduce spasticity by 18%–42% in patients with MS . Both protocols can reduce the level of spasticity by increasing the excitability of the primary motor cortex and as a result increasing the downward inhibitory effects of gamma motoneurons .…”
Section: Introductionmentioning
confidence: 99%
“…Two reviews ( 129 , 130 ) have concluded that, overall, the studies have small sample sizes and varying quality, with PEDro scores ranging from 6 to 10. Thus, they lack the power needed to draw firm conclusions on the effect of FES as an adjunctive treatment with BoNT-A.…”
Section: Concomitant and Adjunctive Therapiesmentioning
confidence: 99%
“…Around 36% of the patients suffered moderate or severe upper limb spasticity (Nam et al, 2019). Weakness, pain, loss of dexterity, stiffness, fibrosis, and atrophy followed by upper limb PSS always contribute to disordered motor control, functional limitations, and poor quality of life that result in an increased burden on caregivers (Leo et al, 2017;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%